Risk of venous thromboembolism in association with factor V leiden in cancer patients - The EDITH case-control study. - Adeline Heraudeau; Aurélien Delluc; Mickaël Le Henaff; Karine Lacut; Christophe Leroyer; Benoit Desrues; Francis Couturaud; Cécile Tromeur (PLoS ONE, 2018)
Cancer and factor V Leiden mutation are both risk factors for venous thromboembolism (VTE). Cancer critically increases the thrombotic risk whereas Factor V Leiden is the most common pro-thrombotic mutation. The impact of the factor V Leiden on the risk of VTE in cancer patients remains uncertain.To assess the impact of factor V Leiden mutation in cancer-associated thrombosis.The EDITH hospital-based case-control study enrolled 182 patients with cancer and VTE as well as 182 control patients with cancer, matched for gender, age and cancer location, between 2000 and 2012, in the University Hospital of Brest. All cases and controls were genotyped for the factor V Leiden mutation and interviewed with a standardized questionnaire.Twenty one of 182 (11.5%) patients with cancer-associated thrombosis carried the factor V Leiden mutation and 4 of 182 (2.2%) controls with cancer but no venous thrombosis. In multivariate analysis including cancer stage and family history of VTE, cancer patients with factor V Leiden mutation had a seven-fold increased risk of venous thromboembolism (adjusted odds ratio [OR], 7.04; 95% CI, 2.01-24.63).The pro-thrombotic Factor V Leiden mutation was found to be an independent additional risk factor for venous thromboembolism in cancer patients and might therefore be considered in the individual thrombotic risk assessment.